Hole Cleaning during Drilling Oil and Gas Wells: A Review for Hole-Cleaning Chemistry and Engineering Parameters - Mohammed Al-Rubaii; Mohammed Al-Shargabi; Dhafer Al-Shehri (Advances in Materials Science and Engineering)
Efficient hole cleaning during drilling operations is critical to maintain a high rate of penetration and smooth drilling, leading to minimum drilling problems and economical drilling efficiency. This process involves several important factors, including pipe-sticking incidents, higher cuttings concentrations in the annulus, noisy vibration of the drill string, erratic equivalent circulating density, lost circulation incidents, well control incidents, geomechanical hole section instability, tight spots during tripping operations, and excessive usage of chemical additives for conditioning hole sections and mud. Various approaches, including correlations, methodologies, developments, algorithms, equipment, charts, field experience, chemicals, and studies involving experiments, can be used to enhance the efficiency of hole cleaning. The development of hole-cleaning models is important for use as hole-cleaning indicators to ensure optimized drilling efficiency. This paper presents a comprehensive overview of the complex field of hole cleaning in the oil and gas industry. It includes techniques, tools, models, and chemical additives. It also encompasses drilling engineering, operations, and chemistry. To facilitate the transit of drill cuttings, maintain hole section stability, cool and lubricate the drill bit, and transmit hydraulic horsepower, this article outlines the important roles of drilling fluids. The significance of chemical additives, including nanoparticles, natural and modified polymers, and synthetic polymers, in preserving wellbore stability, improving drilling efficiency, and lowering drill bit wear is also covered in the study. It concludes by making recommendations for further study to clarify hole cleaning for the reader to facilitate and boost drilling efficiency.